EFEKTIVITAS PEMBANGUNAN SARANA DAN PRASARANA AIR BERSIH DI DESA TANJUNG MEDAN KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI TAHUN 2017 - Pesrianto "; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The study was background by the Interior Minister no. 114 in 2014 regulation on village development guidelines. Planning for village development in a long-term way includes the village's mid-term development plan that is then described in the form of an annual development plan or village RKP. The building of Sustainable Waterproofing and Infrastucrure at Tanjung Medan Village 2017 is find a discrepancy between the village RKP and the village APB on development. The formulation of the problem in this study is how the effectiveness  of sustainable  waterproofing and infrastructure at Tanjung Medan Village 2017.            The study aims to learn of the effectiveness of Sustainable waterproofing and infrastructure at Tanjung Meda village 2017. The research  method used in this study is a qualitative approach with a descriptive study. The type of the research data is the primary and secondary data.  The data collection techniques in this researchs are documenting and interviewing. The data analysis technique used is qualitative data analysis.            The results of this study show that the effectiveness of Sustainable waterproofing and infrastructure at Tanjung Medan  is not effective because of the inadequate benefit of the program, the lack of socialization, the attainment of ill-suited gols, the failure of monitoring of the quality of execution and adaption to planing.     Keywords: Target accuracy , socialization, goals, program monitoring